Size influences the cytotoxicity of poly (lactic-co-glycolic acid) (PLGA) and titanium dioxide (TiO2) nanoparticles - Xiong, Sijing (2013)
The aim of this study is to uncover the size influence of poly (lactic-co-glycolic acid) (PLGA) and titanium dioxide (TiO2) nanoparticles on their potential cytotoxicity. PLGA and TiO2 nanoparticles of three different sizes were thoroughly characterized before in vitro cytotoxic tests which included viability, generation of reactive oxygen species (ROS), mitochondrial depolarization, integrity of plasma membrane, intracellular calcium influx and cytokine release. Size-dependent cytotoxic effect was observed in both RAW264.7 cells and BEAS-2B cells after cells were incubated with PLGA or TiO2 nanoparticles for 24 h. Although PLGA nanoparticles did not trigger significantly lethal toxicity up to a concentration of 300 μg/ml, the TNF-α release after the stimulation of PLGA nanoparticles should not be ignored especially in clinical applications. Relatively more toxic TiO2 nanoparticles triggered cell death, ROS generation, mitochondrial depolarization, plasma membrane damage, intracellular calcium concentration increase and size-dependent TNF-α release, especially at a concentration higher than 100 μg/ml. These cytotoxic effects could be due to the size-dependent interaction between nanoparticles and biomolecules, as smaller particles tend to adsorb more biomolecules. In summary, we demonstrated that the ability of protein adsorption could be an important paradigm to predict the in vitro cytotoxicity of nanoparticles, especially for low toxic nanomaterials such as PLGA and TiO2 nanoparticles.